2019
DOI: 10.1177/1479164119883978
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of angiotensin type 2 receptor prevents endothelial nitric oxide synthase glutathionylation and nitration in ischaemic abductor muscle of diabetic mice

Abstract: Peripheral artery disease is a severe complication of diabetes. We have reported that the deletion of angiotensin type 2 receptor in diabetic mice promoted vascular angiogenesis in the ischaemic muscle 4 weeks following ischaemia. However, the angiotensin type 2 receptor deletion beneficial effects occurred 2 weeks post surgery suggesting that angiotensin type 2 receptor may regulate other pro-angiogenic signalling pathways during the early phases of ischaemia. Nondiabetic and diabetic angiotensin type 2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…We have previously demonstrated that crucial factors involved in the angiogenic processes, such as VEGF, are affected in diabetes ( 7 , 25 ). To determine and understand if apelin can improve endothelial function under a hyperglycemic milieu, we have evaluated its role on critical steps involved in blood vessel formation and compared its response to VEGF-A.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that crucial factors involved in the angiogenic processes, such as VEGF, are affected in diabetes ( 7 , 25 ). To determine and understand if apelin can improve endothelial function under a hyperglycemic milieu, we have evaluated its role on critical steps involved in blood vessel formation and compared its response to VEGF-A.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that crucial factors involved in the angiogenic processes, such as VEGF, are affected in diabetes 7,25 . To evaluate and understand if apelin can improve endothelial function under a hyperglycemic milieu, we have evaluated its role on critical steps involved in blood vessel formation and compared its response to VEGF-A.…”
Section: Resultsmentioning
confidence: 99%
“…AGTR2 [68], MUC5AC [70] and ATP12A [84] are a potential targets for IPF therapy. CYP1A1 [85], HHIP (hedgehog interacting protein) [86], AGTR2 [87], CYP2A6 [88] and PCK1 [83] expression had been confirmed in diabetes mellitus. In the light of important roles in cells, these DEGs in IPF might represent potential prognostic, diagnostics biomarkers and/or therapeutic targets for IPF.…”
Section: Discussionmentioning
confidence: 99%